Pengaruh Dana Pihak Ketiga (DPK), Capital Adequacy Ratio (CAR), dan Non Performing Financing (NPF) terhadap Profitabilitas Bank Syariah dengan Pembiayaan sebagai Variabel Intervening - Setiawan, Ulin Nuha Aji; Indriani, Astiwi (Faculty of Economics and Business Diponegoro University, 2016)
The aim of this resesearch is to identify and analyze the determinant of Profitability in sharia banking of Indonesia in the period of 2011-2015. Profitability is dependent variabel in this research. There are three independent variables that used, wich are Third Party Funds, Capital Adequacy Ratio, Non Performing Financing, and an intervening variabel which is Financing.Sampling technique used is pruposive sampling, obtained by amount 5 sharia banking for sample from 11 syariah banking in Indonesia period 2011-2015. The data analyzed with path analysis using SPSS program. The result of this research show that Non Performing Financing (NPF) and Capital Adequacy Ratio (CAR) has negative influance significant to financing, Third Party Funds have positive influance and not significant to financing. Third Party Funds and Financing has positive influance significant to Profitability, Non Performing Financing (NPF) have negative influance significant to profitability, and then Capital Adequacy Ratio (CAR) have negative influance not significant to Profitability. But, Financing can not mediate influance beetwen variable independent Third Party Financing, Capital Adequacy Ratio (CAR), and Non Performing Financing (NPF) to Profitability.